Complex Interventions Deserve Complex Evaluations: A Transdisciplinary Approach to Evaluation of a Preventive Personalized Medicine Intervention - Garton, Elise M.; Savaş, Serdar; Pell, Christopher; Syurina, Elena V.; Stronks, Karien; Cesuroglu, Tomris (Frontiers in Public Health, 2022)
Non-communicable diseases (NCDs) are the largest cause of disability and death globally. The human and financial costs of NCDs have raised questions of sustainability for many health systems. Personalized, preventive health interventions are an innovative way to address NCDs, but it is difficult to measure their effectiveness using standard evaluation methods. This article describes a novel approach to evaluation by coupling transdisciplinary methods with realist theory to design and pilot a health outcomes evaluation for a personalized medicine approach to NCD prevention in Istanbul, Turkey. Research and practice stakeholders contributed to study design, research questions, validation of results, and recommendations through interactive workshops, consistent dialogue, and reflection. They co-created a customized outcome measurement framework and recommendations that promote sustainability and continuous improvement of future evaluations. The participatory methods helped resolve the dichotomy between patient, practitioner, and researcher focus in the evaluation and improved stakeholders' data literacy. This research contributes to the body of evidence advocating for the use of non-standard methods such as transdisciplinary research to evaluate the effectiveness of complex interventions. The results of the pilot evaluation are also presented as a case study.